Fatores determinantes da dor de dente e o impacto na vida diária de indivíduos residentes em Betim-MG/2012 - Aline Mendes Silva (2012)
The aim of the present thesis was to determine the prevalence of impact from toothache and determinant factors in adults aged 35 to 44 years in the city of Betim (southeastern Brazil). Two cross-sectional studies were carried out to investigate toothache and its impact on daily living and quality of life. A questionnaire was administered to 744 individuals. Dental caries were evaluated using the DMFT index, with toothache in the previous six months considered the outcome. In the first study, variables related to toothache were analyzed based on access to oral health services, toothache severity and social/functional limitations. Sixty-eight percent of the sample had insufficient access to dental services, 39.7% had severe toothaches and 47.3% experienced a substantial impact on daily living. The most frequent consequences of toothache were anxiety/irritation (87.2%) and difficulty chewing (72.6%). The correspondence analysis revealed four groups with distinct profiles and associated factors. Two groups experienced greater impact from toothache on daily living: one composed of individuals with lesser access to oral health services (women, mixed race, married, elementary school education, low household income) and one made up of individuals with severe toothache and high impact on social/functional aspects (aged 40 to 44 years, married or widowed, African descent or mixed race, elementary school education). The other two groups experienced lessereffects from toothache on daily living: one composed of individuals with greater access to oralhealth services (men, separated, university education, monthly income greater than R$ 300) and one composed of individuals with mild toothache and low impact on social/functional aspects (age 35 to 39 years, Caucasian, single, high school education). In the second study, quality of life was investigated using the physical, social, psychological and environmental subscales of the WHOQOL-bref questionnaire. Socio-demographic variables, self-care measures, lifestyle, oral hygiene habits, consumption of sweets and use of dental services were also analyzed. Associations between toothache and the independent variables were determined using logistic regression analysis. The prevalence of toothache was 24.6%. The odds of having a toothache were greater among individuals with poor quality of life on the physical (OR: 1.73; 1.06-2.81), psychological (OR: 1.72; 1.08-2.77) and environmental (OR: 1.65; 1.04-2.62) subscales. Low per capita income (OR: 1.79; 1.15-2.80) and dental caries (OR: 1.74; 1.13-2.71) were also associated with toothache. Individuals who visited the dentist in the previous year had lower odds of experiencing toothache (OR: 0.46;0.29-0.72). The findings indicate that dental caries, income and physical, psychological and environmental domains are important factors in toothache and its impact on quality of life. Thus, such factors should be considered when establishing strategies and policies directed at the oral health of the adult population in Brazil. A case-control study was also carried out to investigate determinant factors of toothache. For such, a subsample of 516 adults was selected (172 cases and 344 controls at a proportion of 1:2, matched for gender, age and neighborhood). The chi-square test was used for the bivariate analysis. Multivariate logistic regression analysiswas used to determine the effect of the independent variables on toothache. Adults who sought out dental assistance (OR=4.19; 95% CI=2.72-6.46), sugar intake > 3 times per day (OR; 2.14 (95% CI; 1.07-4.28) and who had at least one tooth with caries (OR=1.55; 95% CI=1.022.37) presented with a greater chance of feeling dental pain. The final model showed that dental assistance, sugar intake > 3 times per day and dental caries are important factors related to the experience of dental pain.